Market connections: Shea quality - Kantimm, Heino; Kuunyem, Maxwell (Technical Centre for Agricultural and Rural Cooperation, 2011)
A Ghanaian network uses cell phones and specialised software to provide training, microfinance and business support to women producers of shea products.